Description and process evaluation of pharmacists' interventions in a pharmacist-led information technology-enabled multicentre cluster randomised controlled trial for reducing medication errors in general practice (PINCER trial) - Howard, Rachel (Int J Pharm Pract, 2014)
OBJECTIVE: To undertake a process evaluation of pharmacists' recommendations arising in the context of a complex IT-enabled pharmacist-delivered randomised controlled trial (PINCER trial) to reduce the risk of hazardous medicines management in general practices. METHODS: PINCER pharmacists manually recorded patients' demographics, details of interventions recommended, actions undertaken by practice staff and time taken to manage individual cases of hazardous medicines management. Data were coded, double-entered into SPSS version 15 and then summarised using percentages for categorical data (with 95% confidence interval (CI)) and, as appropriate, means (± standard deviation) or medians (interquartile range) for continuous data. KEY FINDINGS: Pharmacists spent a median of 20 min (interquartile range 10, 30) reviewing medical records, recommending interventions and completing actions in each case of hazardous medicines management. Pharmacists judged 72% (95% CI 70, 74; 1463/2026) of cases of hazardous medicines management to be clinically relevant. Pharmacists recommended 2105 interventions in 74% (95% CI 73, 76; 1516/2038) of cases and 1685 actions were taken in 61% (95% CI 59, 63; 1246/2038) of cases; 66% (95% CI 64, 68; 1383/2105) of interventions recommended by pharmacists were completed and 5% (95% CI 4, 6; 104/2105) of recommendations were accepted by general practitioners (GPs), but not completed at the end of the pharmacists' placement; the remaining recommendations were rejected or considered not relevant by GPs. CONCLUSIONS: The outcome measures were used to target pharmacist activity in general practice towards patients at risk from hazardous medicines management. Recommendations from trained PINCER pharmacists were found to be broadly acceptable to GPs and led to ameliorative action in the majority of cases. It seems likely that the approach used by the PINCER pharmacists could be employed by other practice pharmacists following appropriate training.